Autoimmune Hepatitis: Progress from Global Immunosuppression to Personalised Regulatory T Cell Therapy - Nwe Ni Than; Hannah C. Jeffery; Ye H. Oo (Canadian Journal of Gastroenterology and Hepatology)
Autoimmune hepatitis (AIH) is an immune mediated liver injury. The precise aetiology of AIH is still unknown but current evidence suggests both genetic and environmental factors are involved. Breakdown in peripheral self-tolerance, and impaired functions of FOXP3+ regulatory T cell along with effector cell resistance to suppression at the tissue level seem to play an important role in AIH immunopathogenesis. AIH is predominantly a T lymphocytes driven disease but B lymphocytes are also involved in the immunopathology. Innate immune cells are crucial in the initial onset of disease and their response is followed by adaptive T (Th1, Th17, and cytotoxic T cells) and B cell responses evidenced by liver histology and peripheral blood serology. Standard treatment regimens involving steroid and immunosuppressive medications lead to global immune suppression requiring life-long therapy with many side effects. Biologic therapies have been attempted but duration of remission is short-lived. Future direction of diagnosis and treatment for AIH should be guided by “omics” and the immunology profile of the individual patient and clinicians should aim to deliver personalised medicine for their patients. Cell therapy such as infusion of autologous, antigen-specific, and liver-homing regulatory T cells to restore hepatic immune tolerance may soon be a potential future treatment for AIH patients.